LICENCJE WOLNEGO OPROGRAMOWANIA - Gawrysiak, Piotr (Zeszyty Prawnicze, 2017)
Open Source Software Licences Summary Computer software is regarded in popular culture as a typical consumer good. Legally, it constitutes however an example of a „content”, which is protected – in a way not dissimilar to literary or audio-visual works – by copyright law. An important property of these works, closely related to recent advances in computer science and resulting ease of digitization and duplication, is a possibility of costless duplication. This allows the creator of a digital work – for example a computer program – to distribute it at no cost, hence the const of duplication itself is either minimal or even non-existent. In recent years, an emergence of a new content distribution philosophy can be observed. Its proponents postulate, that it should be possible to create such computer software, that would be available for everyone to use, modify and redistribute – all that at no cost. This paper introduces the concept of free software and discuses some legal aspects of its creation and distribution. An overview of the construction of the most popular free software licence, the GNU General Public License is also included.